Seismic performance evaluation of stone masonry wallet - Paras Khati; Hari Ram Parajuli (Journal of Innovations in Engineering Education, 2024)
This study focuses on the seismic performance evaluation of unreinforced stone masonry wall piers in typical residential buildings in Nepal, utilizing the finite element method (FEM). The seismic coefficient method is employed to calculate the horizontal and vertical loads on the masonry wall pier. Key findings indicate that the wall piers are more vulnerable to shear failure and diagonal tension compared to toe crushing and rocking failures. The failure modes suggest that stone masonry buildings in Nepal typically fail due to shear and tension during earthquakes. From this analysis the shear stress reached 1.67 N/mm2 at the end of the load steps. Additionally, a simplified micro-analysis reveals the in-depth behavior and local failure mechanisms of the masonry under seismic loads.